Contribuição do atendimento à distância na adaptação do aparelho de amplificação sonora individual em adultos e idosos - Fiaschi, Bárbara Angelo (2024)
The use of remote care in hearing health has several advantages for professionals, patients, and health systems, including greater ease of care and cost savings, both for residents in distant areas and for people with some mobility limitations. Objective: To analyze the benefits of remote care in relation to the number of hours and patient satisfaction in relation to the use of hearing aids, considering individual, audiological variables, and number of service returns. Method: The research subjects were 97 patients over the age of 18 who received hearing aids in 2023 in a Specialized Rehabilitation Center affiliated with the SUS. For the first group, in-person assistance was offered to adapt the hearing aid and for the second group, remote assistance was offered. The G1 subjects returned after approximately 30 days for the first return visit. The G2 subjects who agreed to participate in the remote service used the device company's application to contact the service. The subjects were characterized in terms of age, sex, degree of cell phone loss and use and all those who returned answered the IOI-HÁ questionnaire. Results: G1 was composed of 52 subjects, with an average age of 70 years and G2 was initially composed of 46 subjects, with an average age of 73 years; in both groups, the majority were female, with a moderate degree of sensorineural loss. 46 subjects from G1 attended the inperson return and only 13 subjects agreed to participate in the remote consultation. There was no statistical difference in relation to hearing aid use, satisfaction or benefit according to the instrument used. Conclusion: The use of remote assistance can be an alternative for the fitting process of subjects using hearing aids, as it can provide simple information that helps in the successful use of hearing aids, as well as adjustments. More studies are still needed so that this care strategy can be widely used in the population of services covered by the SUS